BlossomBox DIY / Nur Azura Maisarah Kamalruzaman - Kamalruzaman, Nur Azura Maisarah (Universiti Teknologi MARA, Kedah, 2025)
BlossomBox DIY is a storage box template with the purpose to helps people in poverty generate income by assembling and selling the boxes. The project addresses the lack of income opportunities in underprivileged communities by creating a simple, affordable, and easy-to-build product that promotes self-sufficiency. Background research highlights the challenges of poverty and the value of skill-based solutions for improving livelihoods. Inspired by micro-entrepreneurship, the project focuses on designing functional, durable, and marketable storage boxes. Surveys and questionnaires involving community members, sellers, and NGOs helped ensure the design meets user needs and local market demands. The findings show high demand for affordable, easy-to-assemble storage solutions with minimal material costs. Based on participant feedback, the final design is practical, versatile, and visually appealing.